Evaluation of supercritical plant extracts on volatile and non volatile biologically active lipophil components - Lemberkovics, É.; Kéry, Á.; Simándi, B.; Kristóf T., T. Sz.; Kakasy, A.; Szőke, É. (International Journal of Horticultural Science, 2001)
Authors dealt more than ten years with the analysis of supercritical extracts. For extraction (SFE) carbon dioxide was used as supercritical solvent. Fractionation of extracts was carried out by releasing the separations pressure at two stages. The extracts were collected as separate samples successively in time. The traditional extractions were carried out with steam distillation or by using n-hexane and ethanol in Soxhlet apparatus. For the analysis of volatile compounds GC, GC-MS; of non volatile compounds TLC-densitometry and spectroscopic methods were used. The following general characteristics were established comparing the composition of steam distillated oils with that of volatile SFE fractions. The SFE fractions were richer in monoterpene-esters and poorer in alcohols than the essential oils prepared by traditional way (clary sage, lavandel). Regarding the distributi,n of the monoterpene and sesquiterpene compounds, the SFE fractions contained sesquiterpene hydrocarbon in higher percentage than the distillated oils (e.g. 13-caryophyllene in Salvia fruticosa, (3-caryophyllene, ymuurolene, y-cadinene in Ochnum basilicum). Further the proportion of sesquiterpenes increased in SFE fractions collected successively in time.Significant difference was remarkable in respect of the optical rotationability of lovage oil and SFE fraction which was probably caused by the different ratio between the two ligustilid enantiomers. It was verified in some cases that a part of mono- and sesquiterpenes were present originally in a bounded form (glycosides) in plants. Therefore they appeared in essential oil fractions only after previous acidic treatment (Thymus, Origanum species). During the supercritical extraction the azulenogene sesquiterpene lactones did not transform to azulenes (in chamomile, yarrow), but the non volatile SFE fractions of some Asteraceae plant contained sesquiterpene–lacton of unchanged structure in high quantity (e.g. cnicin in blessed thistle, parthenolide in feverfew). Authors obtained also SFE fractions which were rich in triterpenoids and phytosterols (marigold, common dandelion).